Cellulose-Sulfuric Acid as an Efficient Biosupported Catalyst in One-Pot Synthesis of Novel Heteroaryl Substituted 1,4-Dihydropyridines - Manouchehr Mamaghani; Khalil Tabatabaeian; Mohaddesseh Mohammadi; Alireza Khorshidi (Journal of Chemistry)
An efficient method for the synthesis of new heteroaryl substituted dihydropyridine derivatives via a one-pot four-component coupling reaction of heteroaldehyde, 1,3-diketone, ethylacetoacetate, and amonium acetate in the presence of cellulose-sulfuric acid as a biosupported solid acid catalyst was developed. The reaction gave the new derivatives of fused 1,4-dihydropyridines in lower reaction times and excellent yields (85–95%).